Water Footprint Analysis Under Dual Pressures of Carbon Mitigation and Trade Barrier: A CGE‐Based Study for Yangtze River Economic Belt. Issue 3 (8th March 2022) - Fu, Yupeng; Huang, Guohe; Zhai, Mengyu; Li, Jianyong; Pan, Xiaojie
Abstract: Facing the dual pressures of carbon mitigation and trade barrier, it is desired that variations of water footprints (WFs) with the related policy interferences be investigated in Yangtze River Economic Belt (YREB). In this study, a factorial equilibrium WFs model is developed to (a) tackle the interactive effects (on blue‐ and gray‐WFs) of different policy alternatives presented as multiple levels of carbon tax and import tariff; (b) explore the variations of blue‐ and gray‐WFs in specific socio‐economic sectors under multiple scenarios of the dual pressures; and (c) investigate the provincial WFs from the perspective of commodity consumption. It is found that increased import tariffs can boost the WFs of primary energy and resource‐conversion sectors, and can promote inter‐sectoral virtual‐water exchanges; carbon tax can suppress the WFs for most of the sectors, and can result in entirely declined industrial production. Moreover, carbon tax can lead to reduced water productivity in YREB, and thus exacerbate water shortage. Through this research, desired policies for water‐footprint management policies could be identified with maximized socio‐economic and environmental benefits. Key Points: A factorial equilibrium water footprint (WF) model for exploring the contributions of multiple policy alternatives on changes in WFs is proposed High carbon tax may sacrifice China's economy; trade barrier between China and the US may lead to negative impacts on China's food security Carbon tax and trade barrier would reduce the blue WFs in the upper reach and would have opposite effects on the gray WFs in the lower reach